A novel anoikis-related gene prognostic signature and its correlation with the immune microenvironment in colorectal cancer - Xiao, Yu; Zhou, Han; Chen, Yiran; Liu, Libin; Wu, Qian; Li, Hui; Lin, Peicheng; Li, Jinluan; Wu, Junxin; Tang, Lirui (Frontiers in Genetics, 2023)
Background: Anoikis is a type of apoptosis associated with cell detachment. Resistance to anoikis is a focal point of tumor metastasis. This study aimed to explore the relationship among anoikis-related genes (ARGs), immune infiltration, and prognosis in colorectal cancer (CRC). Methods: The transcriptome profile and clinical data of patients with CRC were retrieved from The Cancer Genome Atlas and Gene Expression Omnibus databases. Patients were divided into two clusters based on the expression of ARGs. Differences between the two ARG molecular subtypes were analyzed in terms of prognosis, functional enrichment, gene mutation frequency, and immune cell infiltration. An ARG-related prognostic signature for predicting overall survival in patients with CRC was developed and validated using absolute value convergence and selection operator (LASSO) regression analysis. The correlation between signature risk score and clinicopathological features, immune cell infiltration, immune typing, and Immunotherapy response was analyzed. Risk score combined with clinicopathological characteristics were used to construct a nomogram to assess CRC patients prognosis. Results: Overall, 151 ARGs were differentially expressed in CRC. Two ARG subtypes, ARG-high and ARG-low, were identified and correlated with CRC prognosis. The gene mutation frequency and immune, stromal, and ESTIMATE scores of the ARG-high group were higher than those of the ARG-low group. Moreover, CD8, natural killer cells, M1 macrophages, human leukocyte antigen (HLA) and immune checkpoint-related genes were significantly increased in the ARG-high group. An optimized 25-gene CRC prognostic signature was successfully constructed, and its prognostic predictive ability was validated. High-risk score was correlated with T, N, M, and TNM stages. Risk scores were negatively correlated with dendritic cells, eosinophils, and CD4 cells and significantly positively correlated with regulatory T cells. Patients in the high-risk group were more likely to exhibit immune unresponsiveness. Finally, the nomogram model was constructed and showed good prognostic predictive power. Conclusions: ARGs are associated with clinicopathological features and the prognosis of CRC and play important roles in the immune microenvironment. Herein, we underpinned the usefulness of ARGs in CRC to develop more effective immunotherapy techniques.